Residues of different gel formulations on dentinal walls: a SEM/EDS analysis - Nascimento, Angela Longo do; Busanello, Fernanda Hoffmann; Só, Marcus Vinícius Reis; Kuga, Milton Carlos [UNESP]; Pereira, Jefferson Ricardo; Grecca, Fabiana Soares (Wiley, 2015)
The aim of this study was to evaluate the presence of residues of sodium hypo-chlorite gel, chlorhexidine gel, and EDTA gel on dentina l walls after canal preparat ion throughchemical SEM- elemental chemical microanal ys is (EDS) analysis. Forty-eight single-rootedteeth were selected. They had their crowns sectioned and were instrumented with a reciprocat-ing system. The canals were irrigated with 5 mL of saline solution during root canal preparation.After instrumentation, the root canals were irrigated with 3 mL 17% EDTA followed by 1 min ofultrasonic passive activation (33 20 sec) to remove the smear layer, and then irrigated with3 mL of saline solution. The specimens were randomized into three groups (n 5 12) accord ing tothe chemical substance that ﬁlled the root canal for 30 min: GI: 5.5% sodium hypochlorite gel;GII: 2% chlorhexidine gel; GIII: 24% EDTA gel; Negative c ontrol group: no substance was used.Then, the root canals were irrigated with 6 mL of saline solution followed by 1 min of ultrasonicpassive activation (33 20 sec). After ultrasonic activation , the canals were irrigated with 2 mLsaline. The roots were sect ioned, and the perce ntage of each chemical element present in thesamples was analyzed through chemi cal SEM-EDS microanalysis. All expe rimental groupsshowed a signiﬁcantly higher percentage of chemical elements (Na and/or Cl) than the controlgroup (P < 0.03). This in vitro study has shown that, regardless of chemical solutions used evenafter the ﬁnal irrigation protocol, chemical residues of d ifferent substances remained attached tothe r oot c anal wa lls. Microsc. Res. Tech. 78:495–49 9, 2015.
Keywords: Endodontics; Sodium hypochlorite; Chlorhexidine; EDTA; Electron probe microanalysis